2022
DOI: 10.3390/molecules27061855
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activity of Pulcherrimin from the Meschnikowia pulcherrima Clade

Abstract: Pulcherrimin is a secondary metabolite of yeasts belonging to the Metschnikowia pulcherrima clade, and pulcherrimin formation is responsible for the antimicrobial action of its producers. Understanding the environmental function of this metabolite can provide insight into various microbial interactions and enables the efficient development of new effective bioproducts and methods. In this study, we evaluated the antimicrobial and antiadhesive action of yeast pulcherrimin, as well as its protective properties u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…Pulcherrimin is known to be an iron chelator. Previous studies have shown that secreted pulcherrimin caused localized iron depletion in the media (17,44). Results from our transcriptome pro ling show that many iron homeostasis genes were downregulated in the pulcherrimin mutant, including the entire bacillibactin biosynthetic operon (dhbABCEF), bacillibactin transport genes (feuABC, fhuBCG) and the bacillibactin esterase gene besA (Fig.…”
Section: Resultsmentioning
confidence: 69%
“…Pulcherrimin is known to be an iron chelator. Previous studies have shown that secreted pulcherrimin caused localized iron depletion in the media (17,44). Results from our transcriptome pro ling show that many iron homeostasis genes were downregulated in the pulcherrimin mutant, including the entire bacillibactin biosynthetic operon (dhbABCEF), bacillibactin transport genes (feuABC, fhuBCG) and the bacillibactin esterase gene besA (Fig.…”
Section: Resultsmentioning
confidence: 69%
“…Pulcherrimin is known to be an iron chelator. Previous studies have shown that secreted pulcherrimin caused localized iron depletion in the media 21,51 . Results from our transcriptome profiling show that many iron homeostasis genes were downregulated in the pulcherrimin mutant, including the entire Fig.…”
Section: Synthesis Of Pulcherriminic Acid Remains Constitutive Upon C...mentioning
confidence: 98%
“…In this way, Fertinagro Biotech has found an extract from the natural yeast Metschnikowia pulcherrima that exhibits urease inhibitory capacity . In the literature, the antifungal and antimicrobial properties of M. pulcherrima have been described. According to the literature, these properties are caused by the characteristic red pigment found in this yeast, named pulcherrimin. Pulcherrimin ( 1 ) is a polymeric Fe­(III) chelate of pulcherriminic acid ( 2 ). , M. pulcherrima biosynthesizes pulcherriminic acid from the cyclic dipeptide of l -leucine ( 3 ).…”
Section: Introductionmentioning
confidence: 99%